Students' Ability To Think Mathematically in Solving PISA Mathematics Problems Content Change and Relationship - Wisnu Siwi Satiti; Kartika Wulandari (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
This article describes students’ mathematical-thinking process in solving PISA-model mathematics -problems. Mathematical-thinking is not only important for academic succes, but is also esssential for developing mathematical reasoning and critical thinking habits in sustainable development for creating better life. In order to achieve the research aims, we used a qualitative approach with descriptive methods. Data were collected using mathematical activities adapted from PISA items. Three students’ works that represent each level of mathematical ability were selected for in-depth analysis. The findings shows that students’ mathematical-thinking ability in solving PISA-model mathematics-problems is determined by how the students go beyond phases of mathematical-thinkng proses (Entry, Attack, Review). Students can solve problems correctly if they are able to go through all phases, although not all aspects of each phase are fulfilled. If students fail in the Entry phase, it is certain that they cannot go through the next two phases properly (Attack and Review).